2019
DOI: 10.1111/1467-9566.12876
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dissonance and negotiations of biomedicalisation: mental health practitioners’ resistance to theDSMtechnology and diagnostic standardisation

Abstract: Previous research demonstrates that biomedicalisation and diagnostic processes are intertwined in American mental health care, but few studies examine practitioners’ negotiations. This study examines how Mental Health Practitioners (MHPs) negotiate the Diagnostic and Statistical Manual (DSM), diagnosis, standardisation and biomedicalisation‐in‐practice. Feminist grounded theory analysis of 42 semi‐structured interviews with licensed adolescent MHPs reveals accounts of discursive, everyday resistance to the DSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Uncertainty and reservation amongst clinicians and patients may, for example, be central to the diagnostic process, particularly in cases such as ADHD for which objective tests are absent and some scepticism (both medical and public) remains (Rafalovich, 2005). Tensions may arise between a clinician's professional orientation, diagnostic guidelines, and coding practices for insurance (Nelson, 2019). Children and their caregivers are equally situated in sociocultural circumstances which may promote or impede biomedical responses to behaviours related to a diagnosis (Bergey et al, 2018; Conrad & Bergey, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty and reservation amongst clinicians and patients may, for example, be central to the diagnostic process, particularly in cases such as ADHD for which objective tests are absent and some scepticism (both medical and public) remains (Rafalovich, 2005). Tensions may arise between a clinician's professional orientation, diagnostic guidelines, and coding practices for insurance (Nelson, 2019). Children and their caregivers are equally situated in sociocultural circumstances which may promote or impede biomedical responses to behaviours related to a diagnosis (Bergey et al, 2018; Conrad & Bergey, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is hard to gauge what health providers will do with the diagnostic labels made available to them. One might assume that clinicians necessarily take their cues from formal nosologies, but studies have shown that clinicians often resist their logics or negotiate their use of them (Armstrong, 2011;Nelson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 World Health Organization global survey looked at attitudes about diagnostic classifications more broadly, finding psychologists value them to inform treatment and facilitate communication but prefer flexible diagnostic guidelines over strict criteria and worry about culture bias (Evans et al, 2013). Research on other professions shows, not surprisingly, that psychiatrists generally hold a positive view of DSM (Jampala et al, 1992; Junek, 1983; Kortan et al, 2000; Maser et al, 1991; Setterberg et al, 1991; Someya et al, 2001), while social workers and counselors use it and appreciate its scientific and practical benefits but are concerned about potential bias, stigmatization, medicalization, and over-pathologizing (Frazer et al, 2009; Gayle & Raskin, 2017; Hitchens & Becker, 2014; Nelson, 2019; Newman et al, 2007; Probst, 2012; Strong et al, 2012).…”
Section: Psychologist Attitudes Toward the Dsmmentioning
confidence: 99%